Stimulation from 0 to 2 years (Journal of Parents and Teachers, 1995)
It is proposed to initiate a “School for Parents” to empower parents in the education of their children, highlighting their crucial role in intellectual and emotional development. Proper stimulation can enhance neural connections, improving early learning. The program includes physical exercises and activities that have shown positive results in child development.
Keywords: school; play; stimulation; child development